Pharmacological Mechanism of Blood Activating Drug Astragalus Membranaceus in the Treatment of Diabetes Peripheral Vascular Disease - Zhao, Yuying; Su, Hongxia (Journal of Contemporary Medical Practice, 2025)
Diabetes, as a disease characterized by chronic progressive increase of blood sugar level, is known as “thirst quenching” in the field of traditional Chinese medicine. In clinic, the pathogenesis of diabetes is generally considered to be closely related to heredity, diet, mood, obesity and other factors. In recent years, with the development of social economy, people’s lifestyle has gradually changed, making diabetes one of the chronic diseases threatening human health worldwide. In addition, the number of people with diabetes peripheral vascular disease is on the rise, while in the treatment of diabetes and its complications, traditional Chinese medicine shows significant advantages. Astragalus membranaceus, as a kind of traditional Chinese medicine, has the effects of tonifying qi, promoting yang, promoting water, detumescence, supplementing health and strengthening appearance, and has been widely used in the clinical treatment of diabetes. This article reviews the main components and pharmacological effects of Astragalus membranaceus, analyzes the mechanism of Astragalus membranaceus in treating peripheral vascular diseases of diabetes, and explores the clinical progress of Astragalus membranaceus in treating diabetes.